Sejarah Pendidikan Islam Mengulas Perjalanan Dari Masa Klasik, Pertengahan Hingga Masa Modern - Nelly Nelly (Journal on Education, 2024)
The story about the development of Islamic education is an explanation of how Islamic education developed over time, including in terms of concepts, ideas, institutions and implementation from the time of the Prophet Muhammad to the present. In writing this article, the method used is descriptive analysis. In this process, a study of several reading books was carried out and from this research, a conclusion was drawn. It was found that classical Islamic education began during the time of the Prophet Muhammad SAW, and this education developed rapidly along with the development of the Islamic region. This can be seen from the increase in the number of educational figures, materials, methods, models and educational venues that are increasingly developing. In the Middle Ages, Islamic education was not as strong as educational progress in Europe. Education only emphasizes religious knowledge, does not focus on general knowledge. In modern times, Islamic education has begun to experience significant development and plays a role in eliminating colonial rule. Renewal in the Islamic world has emerged through the process of integrating Islamic principles into modern secular science. This effort tries to formulate Islamic education that is based on pure sources of Islamic teachings, and involves reforms in education that focus on the spirit of nationalism.